2021
DOI: 10.3389/fphar.2021.670785
|View full text |Cite
|
Sign up to set email alerts
|

Co-Treatment With Verapamil and Curcumin Attenuates the Behavioral Alterations Observed in Williams–Beuren Syndrome Mice by Regulation of MAPK Pathway and Microglia Overexpression

Abstract: Williams–Beuren syndrome (WBS) is a rare neurodevelopmental disorder characterized by a distinctive cognitive phenotype for which there are currently no effective treatments. We investigated the progression of behavioral deficits present in WBS complete deletion (CD) mice, after chronic treatment with curcumin, verapamil, and a combination of both. These compounds have been proven to have beneficial effects over different cognitive aspects of various murine models and, thus, may have neuroprotective effects in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…The treatment was administered following the protocols previously used by the group (Ortiz-Romero et al, 2021). Vehicle control group (VEH) consisted of WT and CD mice drinking water with 1% DMSO.…”
Section: Treatment Administration and Intakementioning
confidence: 99%
See 2 more Smart Citations
“…The treatment was administered following the protocols previously used by the group (Ortiz-Romero et al, 2021). Vehicle control group (VEH) consisted of WT and CD mice drinking water with 1% DMSO.…”
Section: Treatment Administration and Intakementioning
confidence: 99%
“…We previously reported that only the combined (CURVER) and no the single treatment with CUR and VER significantly improved the cognitive phenotype of CD mice (Ortiz-Romero et al, 2021). Subsequently, we next aim was to evaluate if the combinatorial treatment could represent an effective pharmacological strategy to treat cardiovascular alterations in CD mice, as well as, the role of the XOR as another important source of oxidative stress in WBS .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete deletion (CD) mouse model, carrying the most common deletion found in WBS patients (from Gtf2i to Fkbp6 ), presents a pathological cardiovascular phenotype very similar to that seen in patients with SVAS, hypertrophic cardiopathy and hypertension [ 4 , 5 ]. Moreover, the CD mouse model is the most suitable for assaying potential new therapeutic interventions [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that only the combined (CURVER) and not a single treatment (CUR or VER) significantly improved the cognitive dysfunction of CD mice [ 6 ]. We then evaluated whether the combinatorial treatment could also represent an effective pharmacological strategy to treat cardiovascular alterations in CD mice, as well as studying the role of XOR as it is an important source of oxidative stress in the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%